Case report: Therapeutic response to lorlatinib in advanced large-cell neuroendocrine carcinoma of the lung and breast cancer: a heterochronous double malignancy perspective - Mu, Xiaoli; Li, Yan (Frontiers in Pharmacology, 2024)
Background: Driver mutations in tyrosine kinases, such as the anaplastic lymphoma kinase (ALK) mutation, are known to play a critical role in the pathogenesis of nonsmall cell lung cancer (NSCLC) but are rarely observed in large cell neuroendocrine carcinoma (LCNEC). Multiple primary malignancies (MPMs) refer to the occurrence of two or more distinct primary malignancies within the same or different organs and tissues in a single patient, either simultaneously or sequentially.We reported a case of advanced LCNEC as a heterochronous double primary malignancy, following a prior breast cancer diagnosis in a 55-year-old woman. Ten years after achieving remission from breast cancer, the patient was diagnosed with LCNEC, presenting with multiple brain metastases (BMs) after undergoing surgery and adjuvant radiochemotherapy. She tested positive for the ALK fusion gene and received lorlatinib as an initial treatment. After six weeks, there was a significant reduction in the tumor, and the treatment impact was evaluated as a partial response. The treatment has been continued for over 25 months since the initiation of ALK Tyrosine kinase inhibitor (ALK-TKI) therapy.This case suggested that ALK-positive advanced LCNEC patients might benefit from first-line intervention with lorlatinib, particularly for managing brain metastases.